Clinical application of next generation sequencing-based haplotype linkage analysis in the preimplantation genetic testing for germline mosaicisms - Chen, Dongjia; Xu, Yan; Fu, Yu; Wang, Yali; Liu, Yuliang; Ding, Chenhui; Cai, Bing; Pan, Jiafu; Wang, Jing; Li, Rong; Guo, Jing; Zhang, Han; et al. (Orphanet journal of rare diseases, 2023)
Preimplantation genetic testing (PGT) for monogenic disorders (PGT-M) for germline mosaicism was previously highly dependent on polymerase chain reaction (PCR)-based directed mutation detection combined with linkage analysis of short tandem repeats (STRs). However, the number of STRs is usually limited. In addition, designing suitable probes and optimizing the reaction conditions for multiplex PCR are time-consuming and laborious. Here, we evaluated the effectiveness of next generation sequencing (NGS)-based haplotype linkage analysis in PGT of germline mosaicism. PGT-M with NGS-based haplotype linkage analysis was performed for two families with maternal germline mosaicism for an X-linked Duchenne muscular dystrophy (DMD) mutation (del exon 45-50) or an autosomal TSC1 mutation (c.2074C > T). Trophectoderm biopsy and multiple displacement amplification (MDA) were performed for a total of nine blastocysts. NGS and Sanger sequencing were performed in genomic DNA of family members and embryonic MDA products to detect DMD deletion and TSC1 mutation, respectively. Single nucleotide polymorphism (SNP) sites closely linked to pathogenic mutations were detected with NGS and served in haplotype linkage analysis. NGS-based aneuploidy screening was performed for all embryos to reduce the risk of pregnancy loss. All nine blastocytes showed conclusive PGT results. Each family underwent one or two frozen-thawed embryo transfer cycles to obtain a clinical pregnancy, and the prenatal diagnosis showed that the fetus was genotypically normal and euploid for both families. NGS-SNP could effectively realize PGT for germline mosaicism. Compared with PCR-based methods, the NGS-SNP method with increased polymorphic informative markers can achieve a greater diagnostic accuracy. Further studies are warranted to verify the effectiveness of NGS-based PGT of germline mosaicism cases in the absence of surviving offsprings.